MANAGEMENT CONTROL SYSTEMS, E-GOVERNMENT DIGITAL PLATFORM AND JOB PERFORMANCE : THE MODERATING ROLE OF TRANSFORMATIONAL LEADERSHIP - Levana Dhia Prawati; Yvonne Augustine (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
An organization's Management Control System (MCS) is crucial. The environment, technology, organizational size, and business strategy are the factors that determine the Management Control System. The State Treasury and Budget System (SPAN) is one of Indonesia's digital e-government systems. This study aims to examine the impact of Management Control Systems and digital e-government platforms with transformational leadership as a moderator on the productivity of SPAN users in the Indonesian Directorate of Treasury. The successful implementation of the digital platform using the UTAUT model variable. The respondents of this study are 171 respondents as a user of the State Treasury and Budget System (SPAN) digital platform throughout Indonesia at the Ministry of Finance office of the State Treasury Directorate. This study finds that Facilitating Condition, Habit, and Feature-Level of Use have a positive effect on Job Performance, while management control systems and behavioral intentions do not affect Job Performance. Transformational leadership strengthens the influence of Feature-Level of Use on Job Performance. This research shows that in government organizations, the management control system is important in supporting the goals of organizations to provide understanding regarding vision, mission, and goals. In government organizations, there are other agency units like the Internal Compliance and Transformation ambassadors who participated in this area. These units are not usually the highest leadership who provide formal activities. Another implication to enhance employee work performance, a transformational leadership style is required.